Developing an ultrasonic cleaner using pic microcontroller (PIC16F84) /Shahrizar Roslan - 314891 Shahrizar Roslan; Johari Adnan, supervisor; Fakulti Sains (2005)
Project Paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2005